The impact of investment efficiency on firm value and moderating role of institutional ownership and board independence - Mahdi Salehi; Grzegorz Zimon; Arash Arianpoor; Fatemeh Eidi Gholezoo (Journal of Risk and Financial Management, 2022)
This study investigates the impact of investment efficiency on firm value with a moderating role of institutional ownership and board independence for companies listed on the Tehran Stock Exchange (TSE). The information from 177 companies in 2014-2021 was examined. Tobin's Q is a common measure for firm value, and it is a market-based measure and provides a good tool of comparison. The results show that investment efficiency has an impact on firm value. In addition, institutional ownership and board independence moderate this impact. There is a gap between the impact of investment efficiency on firm value and the moderating role of institutional ownership and board independence. This gap creates an opportunity for carrying out in-depth research on those variables. Since the impact of investment efficiency on firm value emphasizing the role of institutional ownership and board independence has not been studied, the study's findings can show the importance and necessity of this study and fill the gap in this field.
Keywords: 650; board independence; firm value; institutional ownership; investment efficiency